Technology-Based Startup: A Formula to Become Sustainable Company in Indonesia, A Case Study From UAVINDO Nusantara - Uruqul Nadhif Dzakiy (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2018)
Beside technology-based startups are not many enough in Indonesia, they must have faced problems that make them hard to grow. Not many of them can sustain for a long time. UAVINDO Nusantara is an exception. The company that concern in Unmanned Aerial Vehicle (UAV) technology was founded in 2000 and can survive till now. It passed three periods (building trust, crisis, and rising up) before commits to be a solution provider company in aeronotics that concern in military market. Its change capability of organizational management, its innovation culture, and ability to become trusted company are characteristics for the company to become sustainable. Three factors that shape it like that ; leadership of its manager (director), learning culture inside the company, and ability to maintain its network. Keywords: UAVINDO Nusantara, technology-based startup, Indonesian company, sustainable company.